Cranberry fruit epicuticular wax benefits and identification of a wax-associated molecular marker - Lindsay Erndwein; Joseph Kawash; Sara Knowles; Nicholi Vorsa; James Polashock (BMC Plant Biology, 2023)
Abstract Background As the global climate changes, periods of abiotic stress throughout the North American cranberry growing regions will become more common. One consequence of high temperature extremes and drought conditions is sunscald. Scalding damages the developing berry and reduces yields through fruit tissue damage and/or secondary pathogen infection. Irrigation runs to cool the fruit is the primary approach to controlling sunscald. However, it is water intensive and can increase fungal-incited fruit rot. Epicuticular wax functions as a barrier to various environmental stresses in other fruit crops and may be a promising feature to mitigate sunscald in cranberry. In this study we assessed the function of epicuticular wax in cranberries to attenuate stresses associated with sunscald by subjecting high and low epicuticular wax cranberries to controlled desiccation and light/heat exposure. A cranberry population that segregates for epicuticular wax was phenotyped for epicuticular fruit wax levels and genotyped using GBS. Quantitative trait loci (QTL) analyses of these data identified a locus associated with epicuticular wax phenotype. A SNP marker was developed in the QTL region to be used for marker assisted selection. Results Cranberries with high epicuticular wax lost less mass percent and maintained a lower surface temperature following heat/light and desiccation experiments as compared to fruit with low wax. QTL analysis identified a marker on chromosome 1 at position 38,782,094 bp associated with the epicuticular wax phenotype. Genotyping assays revealed that cranberry selections homozygous for a selected SNP have consistently high epicuticular wax scores. A candidate gene (GL1-9), associated with epicuticular wax synthesis, was also identified near this QTL region. Conclusions Our results suggest that high cranberry epicuticular wax load may help reduce the effects of heat/light and water stress: two primary contributors to sunscald. Further, the molecular marker identified in this study can be used in marker assisted selection to screen cranberry seedlings for the potential to have high fruit epicuticular wax. This work serves to advance the genetic improvement of cranberry crops in the face of global climate change.